Group Intervention in a Therapeutic Community for Persons with Chronic Mental Illnes - Ramaprasad, Dharitri (International Journal of Psychosocial Rehabilitation, 2015)
Psychosocial rehabilitation aims at helping people with chronic mental illness to reduce disabilities and improve capabilit- ies to the maximum extent possible so as to integrate them into the family and the community. Therapeutic community (TC) approach is one of the approaches to rehabilitation. This approach refers to milieu therapy that focuses on creating a supportive environment which by itself is therapeutic. Psychosocial rehabilitation programs following a TC approach are comprehensive programs which offer various therapeutic services and activities. One such intervention is group therapy. The present paper attempts to focus on the role of group therapy in a half way home following the TC approach. Following archival research paradigm, all the documented group therapy sessions from 2008 to 2014 were analysed for their themes and techniques. The results have been discussed in view of the themes and content and techniques and the process. The analysis suggests Theme Centred Interactional approach has been followed. Themes that were frequently focused on are: living skills, social skills and personal issues followed by psycho-education about mental and medical illnesses and family relationships. Techniques include role plays, ‘go round’, group discussions, small group activities, group games and shar- ing and narrating experiences. All of them promoted group interaction and communication. Overall improvement was re- ported as assessed on a standardized progress checklist.